Mutations Investigation Experiment (MIE). - Amondi, Tabitha L. (Tufts Archival Research Center, 2014)
Abstract: The Mutation Investigation Experiment is a project designed to investigate random mutagenesis through the use of DNA repair deficient E-coli XL-1 Red strain and sequencing of a reporter plasmid.